Why do discount rates vary? - Kozak, Serhiy; Santosh, Shrihari (Journal of Financial Economics, 2020)
The price of discount rate risk reveals whether increases in equity risk premia represent good or bad news to rational investors. Employing a new empirical methodology, we find that the price is negative, which suggests that discount rates are high during times of high marginal utility of wealth. Our approach relies on using future realized market returns to consistently estimate covariances of asset returns with the market risk premium. Covariances drive observed patterns in a broad cross section of stock and bond expected returns.